Islamic Accounting on Local Wisdom: Interpreting the Payable Concept in the Bhubuwan Tradition - Driana Leniwati; Merlina Maulida; Tri Wahyu Oktavendi (Share: Jurnal Ekonomi dan Keuangan Islam, 2022)
Bhubuwan is the money-giving tradition during a celebration within the Bangkalan community of Madura, East Java. The funds were deemed payable and must be returned at future events of a similar nature. This study aims to delve into the meaning of ‘payable’ in the Bhubuwan tradition in light of Islamic values such as friendship, brotherhood, trust, generosity, and sincerity. Data is gathered through observation, interviews, and documentation review. The informants are members of the local community who have participated in and comprehended the significance of the Bhubuwan tradition. The data is analyzed qualitatively using Miles and Huberman's four stages. The findings show that the term payable is interpreted in a broader context, not just as an obligation, as the existing accounting concept implies, but also as a family relationship and a measure of mutual tolerance and trust. There is also no additional nominal repayment obligation. The value of trust between communities in debt and credit transactions also supports the fact that this tradition has adopted the concept of sharia accounting over the years and has become a part of the local culture. It is expected that the concept of payable in the Bhubuwan tradition will change how humans view accounting concepts in general, particularly those related to payable.========================================================================================================ABSTRAK - Bhubuwan adalah tradisi pemberian uang dalam suatu acara hajatan pada masyarakat Bangkalan Madura, Jawa Timur. Pemberian tersebut dianggap sebagai ‘hutang’ dan akan dikembalikan pada kejadian serupa di masa yang akan datang. Penelitian ini bertujuan untuk menggali makna hutang dalam tradisi Bhubuwan yang dihubungkan dengan nilai-nilai Islam seperti persahabatan, persaudaraan, kepercayaan, kedermawanan, dan ketulusan. Data dikumpulkan melalui observasi, wawancara, dan telaah dokumentasi. Informan adalah anggota masyarakat setempat yang telah berpartisipasi dan memahami tradisi Bhubuwan. Data dianalisis secara kualitatif dengan menggunakan empat tahapan metode Miles dan Huberman. Temuan penelitian menunjukkan bahwa istilah hutang dalam tradisi ini ditafsirkan dalam konteks yang lebih luas, tidak hanya sebagai kewajiban seperti dalam konsep akuntansi, tetapi juga dimaknai sebagai hubungan keluarga, dan sebagai toleransi dan saling percaya. Selain itu, tidak ada penambahan nominal dalam pelunasan hutang. Nilai kepercayaan antar masyarakat dalam transaksi hutang dan kredit juga mendukung fakta bahwa tradisi ini telah mengadopsi konsep akuntansi syariah selama bertahun-tahun dan telah menjadi bagian dari budaya lokal. Konsep hutang dalam tradisi Bhubuwan diharapkan akan mengubah cara pandang manusia terhadap konsep akuntansi secara umum, khususnya yang berkaitan dengan hutang.